Fast Forward 2 / Resource Book - Black Val; Malderez Angi; Mcnorton Maggy; Parker Sue (Oxford University Press, 1988)
A series of four courses for adult students of English attending intensive courses of 60-80 teaching hours. Introductory Unit, Units 1-12, Phrasal Verbs, Tapescript and Answer Key.